Evaluation of dosimetric predictors of toxicity after IMRT with concurrent chemotherapy for anal cancer. (January 2023) - Lukovic, Jelena; Hosni, Ali; Liu, Amy; Chen, Jasmine; Tadic, Tony; Patel, Tirth; Li, Kecheng; Han, Kathy; Lindsay, Patricia; Craig, Tim; Brierley, James; Barry, Aisling; et al.
Highlights: This observational cohort study identifies dosimetric predictors of toxicity in patients with anal squamous cell carcinoma who were treated with curative intent image-guided intensity-modulated radiation therapy and concurrent chemotherapy. This study helps to define relevant dosimetric parameters to consider in radiation treatment planning to reduce the risk of acute and late toxicity. These dosimetric parameters facilitate individualized predictions of acute and late complication risk. Abstract: Background: This study investigates the impact of dosimetric parameters on acute and late toxicity for patients with anal squamous cell carcinoma (SCC) treated with image-guided intensity modulated radiation therapy (IG-IMRT) and concurrent chemotherapy. Materials and Methods: Patients were enrolled in an observational cohort study between 2008 and 2013 (median follow-up 3.4 years). They were treated with standardized target and organ-at-risk (OAR) contouring, planning, and IG-IMRT. Radiotherapy dose, based on clinicopathologic features, ranged from 45 Gy to 63 Gy to gross targets and 27 Gy to 36 Gy to elective targets. Chemotherapy was concurrent 5-fluorouracil and mitomycin C (weeks 1&5). Toxicity was prospectively graded using NCI CTCAE v.3 and RTOG scales. Logistic regression was used to assess the association between dose/volume parameters (e.g small bowel V5) and corresponding grade 2 + and 3+ (G2+/3 + ) toxicities (e.g. diarrhea). Results: In total, 87 and 79 patients were included in the acute and late toxicity analyses, respectively. The most common acute G2 + toxicities were skin (dermatitis in 87 % [inguino-genital skin], 91 % [perianal skin]) and hematologic in 58 %. G2 + late anal toxicity (sphincter dysfunction), gastrointestinal toxicity, and skin toxicity were respectively experienced by 49 %, 38 %, and 44 % of patients. Statistically significant associations were observed between: G2 + acute diarrhea and small bowel V35; G2 + acute genitourinary toxicity and bladder D0.5cc ; G2 + inguino-genital skin toxicity and anterior skin V35; G2 + perianal skin toxicity and posterior skin V15; G2 + anemia and lower pelvis bone V45. D0.5 cc was significantly predictive of late toxicity (G2 + anal dysfunction, intestinal toxicity, and inguino-genital/perianal dermatitis). Maximum skin toxicity grade was significantly correlated with the requirement for a treatment break. Conclusion: Statistically significant dose-volume parameters were identified and may be used to offer individualized risk prediction and to inform treatment planning. Additional validation of the results is required.